Une analyse de la politique fiscale du gouvernement fédéral par l’examen des soldes budgétaires - Coulombe, Serge (L'Actualité économique, 1984)
ABSTRACTIn this paper, we assess the current federal fiscal policy using the budget forecast of February 1984 and some macroeconomic concepts. The payments of interest on the public debt are of considerable importance in our analysis. We also give our opinion on the macroeconomic impact of a certain number of non budgetary measures included in the Federal budget of February 1984. Finally, we analyse the long term problems brought up by the budget deficits of the Federal government.